A simple approach to obtain comparable Shigella sonnie MLVA results across laboratories - Chiou, C.S.; Izumiya, H.; Thong, Kwai Lin; Larsson, J.T.; Liang, S.Y.; Kim, J.Y.; Koh, X.P. (Elsevier, 2013)
tMultilocus variable-number tandem repeat analysis (MLVA) is a promising subtyping tool to comple-ment pulsed-field gel electrophoresis for discriminating closely related strains of some monomorphicorganisms, including Shigella sonnei, which is one of the major foodborne pathogens. However, MLVAresults are usually difficult to compare directly between laboratories, impeding the application of MLVAas a subtyping tool for disease surveillance and investigation of common outbreaks across regions orcountries. It has long been a big challenge in seeking an approach that can be implemented to obtaincomparable MLVA results across laboratories. By implementing a panel of calibration strains in each par-ticipating laboratory for data normalization, the MLVA results of 20 test strains were comparable eventhough some analytical conditions were different among the laboratories. This approach is simple, pro-tocol independent, and easy to implement in every laboratory, and a small calibration set is sufficient togenerate mathematical equations for accurate copy number conversion